2010 17th Working Conference on Reverse Engineering 2010
DOI: 10.1109/wcre.2010.19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Software Evolution on Software Clustering

Abstract: The evolution of a software project is a rich data source for analyzing and improving the software development process. Recently, several research groups have tried to cluster source code artifacts based on information about how the code of a software system evolves. The results of these evolutionary approaches seem promising, but a direct comparison to traditional software clustering approaches based on structural code dependencies is still missing. To fill this gap, we conducted several clustering experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…In another set of studies [8], [10], [22], [33], [34], researchers evaluate their proposed recovery techniques using authoritative architecture recoveries of several additional systems. Since none of these were ground-truth architectures, it is likely that they suffered from inaccuracies.…”
Section: A Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In another set of studies [8], [10], [22], [33], [34], researchers evaluate their proposed recovery techniques using authoritative architecture recoveries of several additional systems. Since none of these were ground-truth architectures, it is likely that they suffered from inaccuracies.…”
Section: A Related Workmentioning
confidence: 99%
“…Hence, a straightforward architecture recovery method could be to simply consider packages and/or directories to be software components. In fact, this approach has been adopted by some existing work [10], [34]. To evaluate the validity of such a method, we examined the extent to which packages or directories represent the components in the four ground-truth architectures.…”
Section: Packages and Directory Structurementioning
confidence: 99%
“…It is reasonable to assume the package structure to be a good approximation of the decomposition of the system into architecturally significant elements, as packages are created by the developers of the system. In fact, package structuring has been used as a decomposition reference in prior research as well [4]. Therefore, one can say that package structuring of a Java project is representative of Module View architecture in which each architectural module consists of several Java classes (as a package) and the relation between them is is-part-of.…”
Section: A Package Viewmentioning
confidence: 99%
“…for various software engineering tasks. Beck and Diehl [6] found correlation between software evolution and concern clustering. They showed that using evolutionary information along with other information improves the accuracy of concern clustering.…”
Section: Introductionmentioning
confidence: 99%